Effects of trunk rehabilitation with kinesio and placebo taping on static and dynamic sitting postural control in individuals with chronic stroke: A randomized controlled trial. Issue 8 (16th November 2020) - Cho, Yong-Hun; Cho, Kyun; Park, Shin-Jun
ABSTRACT: Background : Impaired trunk postural control is common after stroke. Combining kinesio taping with trunk rehabilitation has been shown to enhance the recovery of postural control ability in patients with stroke. Objective : We investigated whether the combination of kinesio taping with trunk rehabilitation would improve dynamic and static sitting stability after stroke. Methods : Twenty-eight patients with stroke were recruited and randomly assigned to one of the two 8-week trunk rehabilitation programs with kinesio (experimental group) or placebo taping (control group). Outcome measures were dynamic forward, dynamic backward, affected-side, and unaffected-side sway areas, static sway area and length, and the total limit of stability (LOS) area. The variables were measured using the BioRescue analysis system. All outcome measures were assessed at baseline and after 8 weeks of trunk rehabilitation. Results : Significant increases were observed in the dynamic forward, dynamic backward, affected-side, and unaffected-side sway areas, and the total LOS area, in the experimental and control groups, whereas decreases were observed in the static sway area and length. The dynamic forward sway area was significantly higher in the experimental group than in the control group, but there were no significant differences between the groups in the other variables. Conclusions : Trunk rehabilitation is effective for improving dynamic and static sitting stability after stroke. The addition of kinesio taping to the back muscles further increases forward mobility.